The Value of Magnetic Resonance Imaging in Catheter Ablation of Atrial Fibrillation - Gu, Jun (Clin Cardiol, 2015)
Atrial fibrillation (AF) is the most common arrhythmia encountered in clinical practice. Catheter ablation is now a recognized treatment for those with symptomatic AF refractory to drug therapy. Innovations in magnetic resonance imaging (MRI) have empowered clinicians to improve ablation efficacy while reducing the risk of complications. It is demonstrated that late gadolinium enhancement MRI has additional advantages over modalities such as echocardiography and computed tomography, due to its ability to assess the structural remodeling directly. As a result, MRI has become an indispensable imaging tool to personalize the AF ablation strategy, assess the efficacy and potential complications of AF ablation, and guide the repeat procedure.